ASPETAR - Assisting athletes in achieving their full potential (2011)
Aspetar is the first specialised Orthopaedic and Sports Medicine Hospital in the Gulf region. It provides the highest possible medical treatment for sports-related injuries in a state-of-the-art facility, staffed by some of the world`s leading sports medicine practitioners and researchers.